Factors Associated with Delay in Treatment of Cancer - Charan Amogh Raj KR; Manikanta KV; Sudhir; Harish BR (Medsci Publications, 2022)
Introduction: This is a cross sectional study conducted on cancer patients who presented at the peripheral cancer center, Mandya Institute of Medical Sciences, Mandya with an objective to find out the possible factors influencing the delay in treatment of cancer. Method: Each day the patients coming for radiotherapy treatment were selected, based on the inclusion criteria for the study and an informed consent was taken before collecting the data. Data was collected by questionnaire method and was entered in an excel sheet and analyzed. Result: The result revealed that 65% of the patients belonged to the age group 50-69 and that the delay in treatment significantly increased with increase in age, 80% of the patients were not aware and their median delay was about 60 days, 59% of the patients neglected the symptoms and their median delay was about 60 days, and 5 percent of them took self-treatment and their median delay was 60 days. Conclusion: This study, revealed that 4 important factors, all of which belonged to the patient, were responsible for the significant delay in the treatment. The 4 factors were age of the patient, awareness about the symptom, neglecting the symptom and history of self-treatment.